Around the Corner to Better Health: A Milwaukee Corner Store Initiative. Issue 6 (July 2018) - Young, Staci; DeNomie, Melissa; Sabir, JoAnne; Gass, Eric; Tobin, Jessie
Purpose: To discuss successes and challenges of a collaborative pilot project to increase healthy food availability in corner stores in Milwaukee, Wisconsin. The Lindsay Heights Healthy Corner Store Initiative aimed to help corner stores sell high-quality produce by increasing supply of healthy foods and funding minor store upgrades to facilitate change. Design: Evaluation research. Setting: Milwaukee, Wisconsin. Participants: Corner stores; youth and adult community members. Intervention: (1) Supporting businesses in purchasing equipment to stock fresh produce, (2) connecting stores with produce sources, and (3) community outreach and marketing. Measures: Partnership capacity, youth engagement in food justice, and community members' usage of corner stores. Analysis: Qualitative analysis; descriptive statistics. Results: Storeowners reported more sold produce items per week and increased noticeable fresh produce upon entrance into the store. There was increased or improved store redesign, fresh produce signage, in-store cooking demonstrations, and small business development resources. Conclusion: Youth learned about new vegetables, increased kitchen skills and proper food storage, and the effects of obesity on overall health. Similar interventions must address infrastructure costs, cooperation with property owners, and local policies and regulations affecting business practices.